Effect of Selenium Treatment on Central Insulin Sensitivity: A Proteomic Analysis in β-Amyloid Precursor Protein/Presenilin-1 Transgenic Mice - Xu, Xia; Qi, Pishui; Zhang, Ying; Sun, Huihuan; Yan, Yong; Sun, Wenxiu; Liu, Shudong (Frontiers in Molecular Neuroscience, 2022)
Prior studies have demonstrated a closed association between brain insulin resistance and Alzheimer’s disease (AD), while selenium supplementation was shown to improve insulin homeostasis in AD patients and to exert neuroprotective effects in a mouse model of AD. But the mechanisms underlying the neuroprotective actions of selenium remain incompletely understood. In this study we performed a label-free LC-MS/MS quantitative proteomics approach to analyze differentially expressed proteins (DEPs) in the hippocampus and cerebral cortex of APP/PS1 mice following 2 months of treatment with sodium selenate. 319 DEPs (205 upregulated and 114 downregulated proteins) were detected after selenium treatment. Functional enrichment analysis revealed that the DEPs were mainly enriched in processes affecting axon development, neuron differentiation, tau protein binding, and insulin/ insulin-like growth factor type 1 (IGF1)-related pathways. These results demonstrate a number of insulin/IGF1 signaling pathway-associated proteins are differentially expressed in ways that are consistent with reduced central insulin resistance suggesting selenium a therapeutic value in the treatment of neurodegenerative and metabolic diseases such as AD and non-alcoholic fatty liver disease (NAFLD).